SAT0337 EVALUATION OF BODY COMPOSITION AND BONE STATUS ACCORDING TO MICROVASCULAR INVOLVEMENT IN SYSTEMIC SCLEROSIS PATIENTS. (13th June 2020) - Paolino, S.; Gotelli, E.; Casabella, A.; Cattelan, F.; Schenone, C.; Patanè, M.; Pacini, G.; Pizzorni, C.; Sulli, A.; Smith, V.; Cutolo, M.
Abstract : Background: Systemic sclerosis (SSc) is a complex autoimmune connective tissue disease, characterized by autoimmune inflammatory microvascular damage with progressive loss of capillaries, fibrosis and ischemia of skin and internal organs. (1) Nailfold videocapillaroscopy (NVC) is a safe toll for early diagnosis of SSc, it identify morphological changes of vessel that are predictive for clinical disease progression and organ involvement.(2) About clinical complication the loss of bone mass and body composition abnormalities, particularly muscle mass and strength loss (sarcopenia), are recognized in advanced disease.(3) Objectives: To evaluated in SSc patients, the body composition and the bone status according to the microvascular condition, assessed and scored by nailfold videocapillaroscopy (NVC, "Early", "Active", "Late" patterns). Methods: Body composition and bone mineral density (BMD) were assessed by DEXA in 35 female SSc patients classified according to the 2013 EULAR/ACR criteria and 32 sex-matched healthy subjects. Clinical, laboratory, body composition and bone parameters were analysed according to the different NVC patterns. Means were compared by the Student's t test or one way analysis of variance; medians were compared by the Kruskall Wallis test; and frequencies by the chi square test. Results: Higher prevalence of vertebral (26.4%vs 9.3%) and femoral (32.3% vs 9.3%) osteoporosis (OP) was found in SSc. Particularly SSc patients with "Late" NVC pattern showed a significantly higher prevalence of vertebral (p=0.018) and femoral OP (p=0.016). Regional assessment of bone mass (BM) in 7 different body areas showed a significant lower BMD only at the total spine (P=0.008) and femoral neck (p=0.027) in advanced microvascular damage. Patients with "Late" NVC pattern showed lower whole body lean mass (LM) compared to "Early" and "Active" NVC patterns, particularly at upper limbs. To note, in all body sites, BMD correlate with LM and BMC according to NVC pattern severity. Conclusion: SSc patients with most severe microvascular damage show a significantly altered body composition and bone status suggesting a strong link between microvascular failure and associated muscle/bone sufference. References: [1]Cutolo M et al. Expert Rev Clin Immunol 2019; 15(7):753-64 [2]Cutolo M et al. Clin Rheumatol 2019; 38(9):2293-7 [3]Corallo C et al. Rheumatol Int 2019;39(10):1767-75. Disclosure of Interests: Sabrina Paolino: None declared, Emanuele Gotelli: None declared, Andrea Casabella: None declared, Francesco Cattelan: None declared, Carlotta Schenone: None declared, Massimo Patanè: None declared, Greta Pacini: None declared, Carmen Pizzorni: None declared, Alberto Sulli Grant/research support from: Laboratori Baldacci, Vanessa Smith Grant/research support from: The affiliated company received grants from Research Foundation - Flanders (FWO), Belgian Fund for Scientific Research in Rheumatic diseases (FWRO), Boehringer Ingelheim Pharma GmbH & Co and Janssen-Cilag NV, Consultant of: Boehringer-Ingelheim Pharma GmbH & Co, Speakers bureau: Actelion Pharmaceuticals Ltd, Boehringer-Ingelheim Pharma GmbH & Co and UCB Biopharma Sprl, Maurizio Cutolo Grant/research support from: Bristol-Myers Squibb, Actelion, Celgene, Consultant of: Bristol-Myers Squibb, Speakers bureau: Sigma-Alpha